Experimental Evaluation of a Novel Percutaneous Transseptal Catheter-Based Mitral Valve Replacement Technology. (September 2019) - Vahl, Torsten P.; Grogan, Aaron; Cheng, Yanping; Yi, Genghua; von Oepen, Randolf; Khalique, Omar K.; Wallace, Daniel T.; Modine, Thomas; Granada, Juan F.
Abstract : Background: Transcatheter mitral valve replacement is a novel therapeutic approach aiming to treat patients with severe mitral regurgitation. This study aimed to evaluate the biological and technical performance of a novel transseptal transcatheter mitral valve replacement system (Cephea Valve Technologies, Santa Cruz, CA) in a preclinical model. Methods: Biological performance and healing response were evaluated following open-heart surgical implantation procedures in 10 sheep utilizing an antegrade transatrial access. Valve performance was assessed with fluoroscopy, echocardiography, and histology at 30 (n=2), 60 (n=3), and 90 days (n=5). Feasibility of transseptal valve delivery and performance was tested acutely in 10 pigs. Results: In the chronic studies, all animals survived without problems until completion of the study. The hemodynamics of the study valves were excellent with low rates of paravalvular leak. There was no left ventricular outflow tract obstruction. Pathological evaluation showed excellent position and condition of the mitral implants without evidence for thrombosis, endocarditis, or excessive calcification. Subsequently, mitral valves were implanted in 10 pigs using a dedicated transseptal delivery system. The implants remained in stable position with excellent hemodynamic profile. Correct valve position and function was confirmed by echocardiography and autopsy. Conclusions: The transseptal delivery of the Cephea transcatheter mitral valve replacement system in an experimental model was feasible and safe. The chronic studies demonstrated a favorable healing response. Further human studies are needed to evaluate the performance of this novel valve system in patients with severe mitral regurgitation.